2012
DOI: 10.22164/isea.v6i2.69
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Board Independence on the Sustainability Reporting Practices of Large U.S. Firms \

Abstract: As sustainability reporting becomes more commonplace, it is important to understand the factors that influence firms’ voluntary reporting decisions. This exploratory study examines whether board independence affects the sustainability reporting decisions of the 500 largest firms in the United States. We also investigate other factors that may be associated with sustainability reporting, including environmental performance and reputation. We find that<br />firms with a greater proportion of independent bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
2
28
1
4
Order By: Relevance
“…In the case of governance attributes Herda et al (2013) found that board independence explains firm's sustainability reporting decision as well as the likelihood of issuing a higher quality sustainability report. Examining moderating relationship, Sun et al (2010) examined the moderating effect of board size and audit committee on the relationship between earnings management and corporate environmental disclosure.…”
Section: Determinants Of Environmental Disclosurementioning
confidence: 99%
See 2 more Smart Citations
“…In the case of governance attributes Herda et al (2013) found that board independence explains firm's sustainability reporting decision as well as the likelihood of issuing a higher quality sustainability report. Examining moderating relationship, Sun et al (2010) examined the moderating effect of board size and audit committee on the relationship between earnings management and corporate environmental disclosure.…”
Section: Determinants Of Environmental Disclosurementioning
confidence: 99%
“…Magness (2006) further asserts that there have been large inconsistencies between information disclosed an actual performance making the concept of environmental disclosures difficult to define. Also, various terminologies have been used in literature to refer to address environmental issues as it relates to financial reporting for example, environmental disclosure , environmental expenditures (Cho, Freedman, & Patten, 2012), environmental reporting (Buniamin, 2010), sustainability reporting (Herda, Taylor, & Winterbotham, 2013), environmental accounting (Donwa, 2011) and environmental management accounting (Sulaiman & Mokhtar, 2012) etc. Despite the shortcomings, various researchers have attempted to conceptualize the issue.…”
Section: Conceptual Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herda et al. () find that U.S. firms with a greater proportion of independent board members and firms with better environmental performance are more likely to publish sustainability reports.…”
mentioning
confidence: 99%
“…Researchers have applied various theoretical and empirical frameworks to study various dimensions of CSR. Some argue that slack resources enable firms to go for voluntary CSR disclosure [1], while others relate such initiatives with reputational risk [2] and a company's value [3]. The literature focusing on the determinants of CSR disclosure argues that size, profitability, and a desire for legitimacy are the main determining factors of CSR disclosure (see for review [4]).…”
Section: Introductionmentioning
confidence: 99%